ENHANCING THE SAFETY OF EPOXY FLOORING MATERIALS IN WET WORKING CONDITION - Sami, Abdelhalim; Khamaj, Abdulrahman; Ibrahim, A. M. M; Ameer, A K (Journal of King Abdulaziz University: Engineering Sciences, 2022)
Abstract. When a person walks across a floor, static electricity is generated purely by the contact and separation of the soles of the individual’s shoes from the floor. In many industrial processes, electrostatic charges are fully common. They can cause breakdowns, damage, fires, and explosions. On the other side, without enough friction between shoes and flooring materials during walking, a slip is most probable to occur. There is an increasing demand to increase the coefficient of friction between shoes and flooring materials to eliminate slipping and prevent accidents. The present work aims to improve the frictional and electrostatic properties of epoxy as flooring materials for different applications. We proposed the iron machining chip wastes to use as filling materials for epoxy flooring to increase friction coefficient and decrease the electrostatic charge generated from the friction of shoes against flooring materials. The experimental results revealed that a remarkable reduction in static charge was noticed in wet sliding conditions. This behavior is referred to that the water helps for disposal static charge away from the contact surfaces. In presence of shoes “A” with hardness 65 shore A, the maximum values of friction coefficient values observed at epoxy floor containing 1% and 2% iron powder in wet condition. Meanwhile, 4 % iron powder was the optimum condition for reducing electrostatic charge. For shoes “B” with hardness 63 shore A, the maximum values of friction coefficient values were observed at 2% iron powder content. -In presence of shoes “C” with hardness 67 shore A, the maximum values of friction coefficient values were observed at 2% iron powder content.